ANALISIS PENGARUH KUALITAS PELAYANAN JASA PENDIDIKAN TERHADAP KEPUASAN PELANGGAN DI SMK KRISTEN IMMANUEL 1 PONTIANAK (Studi Kasus Pada Siswa-Siswi SMK Kristen Immanuel 1 Pontianak angkatan 2013 dan 2014) - B31111049, Wahyuni (Jurnal Manajemen Update, 2016)
The aim of this study isÂ  to examine and analyze the influence of technical quality, functional quality and corporate image on customer satisfaction at SMK Kristen Immanuel 1 Pontianak. Population in this research is all students of batch 2013 and 2014 SMK Kristen Immanuel 1 Pontianak. The number of samples of this study are 100 students of batch 2013 and 2014. For data analysis, the writer uses multiple linear regression analysis, the coefficient of determination, the t-significance test. The error rate (significance) used in this study is 5%. Prior to the regression analysis, the writer also perform classic assumption test, so this research model is free from problems of multikolienaritas (correlations between variables) and the problem of data normality. All data analysis is performed using IBM SPSS version 20 program. Results of the study found (1) the technical quality has negative and does not have significant effect on satisfaction of Students of SMK Kristen Immanuel 1 Pontianak (2) the functional quality has positive and significant effect on satisfaction of Students of SMK Kristen Immanuel 1 Pontianak (3) the corporate image has positive and significant effect to the satisfaction of Students of SMK Kristen Immanuel 1 Pontianak. Keyword : Technical Quality, Functional Quality, Corporate Image, Satisfaction